Complex Fault Geometry and Rupture Dynamics of the MW 6.5, 30 October 2016, Central Italy Earthquake. Issue 4 (16th April 2018) - Scognamiglio, L.; Tinti, E.; Casarotti, E.; Pucci, S.; Villani, F.; Cocco, M.; Magnoni, F.; Michelini, A.; Dreger, D.
Abstract: We study the 30 October 2016 Norcia earthquake (MW 6.5) to retrieve the rupture history by jointly inverting seismograms and coseismic Global Positioning System displacements obtained by dense local networks. The adopted fault geometry consists of a main normal fault striking N155° and dipping 47° belonging to the Mt. Vettore‐Mt. Bove fault system (VBFS) and a secondary fault plane striking N210° and dipping 36° to the NW. The coseismic rupture initiated on the VBFS and propagated with similar rupture velocity on both fault planes. Updip from the nucleation point, two main slip patches have been imaged on these fault segments, both characterized by similar peak‐slip values ( 3 m) and rupture times ( 3 s). After the breakage of the two main slip patches, coseismic rupture further propagated southeastward along the VBFS, rupturing again the same fault portion that slipped during the 24 August earthquake. The retrieved coseismic slip distribution is consistent with the observed surface breakages and the deformation pattern inferred from interferometric synthetic aperture radar measurements. Our results show that three different fault systems were activated during the 30 October earthquake. The composite rupture model inferred in this study provides evidences that also a deep portion of the NNE trending section of the Olevano‐Antrodoco‐Sibillini thrust broke coseismically, implying the kinematic inversion of a thrust ramp. The obtained rupture history indicates that in this sector of the Apennines, compressional structures inherited from past tectonics can alternatively segment boundaries of NW trending active normal faults or break coseismically during moderate‐to‐large magnitude earthquakes. Key Points: Rupture history of the 30 October 2016 Norcia earthquake is modeled by jointly inverting seismograms and GPS coseismic data Two main slip patches, with similar slip value and rupture times, occur updip from the nucleation on two differently oriented faults This result has implications for dynamic control of segmented fault systems in the Central Apennines due to geological structures inherited from past tectonics